-65-8x=8x+15

Simple and best practice solution for -65-8x=8x+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -65-8x=8x+15 equation:


Simplifying
-65 + -8x = 8x + 15

Reorder the terms:
-65 + -8x = 15 + 8x

Solving
-65 + -8x = 15 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-65 + -8x + -8x = 15 + 8x + -8x

Combine like terms: -8x + -8x = -16x
-65 + -16x = 15 + 8x + -8x

Combine like terms: 8x + -8x = 0
-65 + -16x = 15 + 0
-65 + -16x = 15

Add '65' to each side of the equation.
-65 + 65 + -16x = 15 + 65

Combine like terms: -65 + 65 = 0
0 + -16x = 15 + 65
-16x = 15 + 65

Combine like terms: 15 + 65 = 80
-16x = 80

Divide each side by '-16'.
x = -5

Simplifying
x = -5

See similar equations:

| x^3-2x^2-3x=0 | | -42-3x=6-9x | | 9x^2+24x=-16 | | 3(2x+4)+8=50 | | ax=bx+c | | 4x^2=-12x+10 | | 10a-5b=12 | | x(4x^2-20x+24)=0 | | 8+3x=23 | | 100y+30=120y+90 | | x-6=x+21 | | x-6=x-21 | | 3(3-4d)=57 | | 3x+14=20-2x | | 9s+5=s+7 | | 2c-1=1-2c | | 15x+10=40 | | 5x-95=2x-5 | | .6y=-.75 | | x^4-27x=0 | | f(3)=x^3+2x^2-x-1 | | 10-7x=61-28x | | -66-10x=7x+19 | | 5(m+2)=-4m-8 | | 107-5x=3x+11 | | 107-53=3x+11 | | f(-2)=-x^3+2x^2+x-1 | | 88-3x=9x+16 | | -2y=14-3x | | 5+3x=11+3x | | x=-5y+33 | | 5(m+2)=-4-8 |

Equations solver categories